Analyzing The Correlation of Uric Acid and Fasting Blood Sugar in Type 2 Diabetes Patients: A Study from ODSK Hospital, North Sulawesi, Indonesia - Fathin Gafur; Youla Assa; Murniati Tiho (Graha Primera Saintifika, 2025)
Type 2 diabetes mellitus (T2DM) is a major non-communicable disease in Indonesia and is commonly diagnosed using fasting blood glucose (FBG) levels. Recent studies have suggested a potential association between fasting blood sugar (FBS) and uric acid, which plays a role in oxidative stress and glucose metabolism, although findings have been inconsistent. This study aimed to examine the association between blood uric acid levels and FBG levels in T2DM patients at ODSK Regional Hospital, North Sulawesi, Indonesia, given the rising prevalence of T2DM and related metabolic disorders in the region. A cross-sectional study was conducted using secondary data from medical records of T2DM patients between July 2023 and July 2024. Among male patients, 25 percent had uric acid levels between 3.0 and 7.4 mg/dL, while 28.8 percent had levels above 7.4 mg/dL. Among female patients, 32.7 percent had uric acid levels between 2.1 and 6.3 mg/dL, and 13.5 percent had levels above 6.3 mg/dL. Additionally, 84.6 percent of all patients had FBG levels of 126 mg/dL or higher. Statistical analysis showed no significant correlation between blood uric acid levels and FBG levels (ρ = 0.541; r = 0.541), suggesting that there is no significant association between these two variables in this population.